Rwanda : Eighth Review Under the Policy Support Instrument and Request for Extension, and Third Review Under the Standby Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Rwanda. (IMF Staff Country Reports; Country Report, 2018)
This paper discusses Rwanda's Eighth Review Under the Policy Support Instrument (PSI) and Request for Extension, and Third Review Under the Standby Credit Facility (SCF). The existing PSI and SCF arrangement have supported Rwanda's efforts to address external imbalances, thereby supporting continued strong growth and durable poverty reduction. The SCF arrangement added a financing component to the existing PSI-supported program, which aims to promote private-sector led growth through safeguarding macroeconomic stability, including through external sustainability, fiscal sustainability based on continued improvements in domestic resource collection, low and stable inflation, and enhancing access to credit and deepening the financial sector.